2021
DOI: 10.7860/jcdr/2021/50795.15380
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Analgesic Efficacy of Erector Spinae and Oblique Subcostal Transverse Abdominis Plane Block in Laparoscopic Cholecystectomy

Abstract: Introduction: The pain after Laparoscopic Cholecystectomy (LC) which has both somatic and visceral component. Interfascial plane blocks play a major role in Multimodal Analgesia (MMA). Previous studies have found good analgesic benefits with Erector Spinae Plane (ESP) and Oblique Subcostal Transversus Abdominis Plane (OSTAP) blocks. However, till date no study exists which compares the above blocks with addition of dexamethasone. Aim: To compare ESP with OSTAP block using low concentration of Local Anaestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In the present study, feedback regarding post-operative pain relief was collected after the patient's discharge from the hospital. Similar to Sahu et al significantly more patients from the ESPB group were satisfied in comparison to the OSTAP group [13].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the present study, feedback regarding post-operative pain relief was collected after the patient's discharge from the hospital. Similar to Sahu et al significantly more patients from the ESPB group were satisfied in comparison to the OSTAP group [13].…”
Section: Discussionsupporting
confidence: 79%
“…Sahu et al in their RCT compared the efficacy of ESPB and OSTAPB at T7 but did not find any significant difference in intraoperative opioid requirement between the groups, whereas there was a statistically significant difference in the mean VAS between the groups, which remained significantly lower in the ESP group during the first 24 hours as compared to OSTAPB. They concluded that ESPB was a superior block for laparoscopic cholecystectomy in comparison to OSTAPB [ 13 ]. In the present study, the patients in group O demanded tramadol significantly more times than those in group E, and the first analgesic demand was significantly delayed in group E (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, five studies were excluded because of the pediatric population, two articles were excluded due to retrospective study, two for commentary, and one for conference abstract. Therefore, 15 RCTs involving 947 patients were included in this systematic review and meta-analysis [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], and the detailed flow diagram is presented in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, the addition of a lesser amount of Dexamethasone 1 mcg to 0.5% Ropivacaine does not result in any significant change [ 88 ]. Again, the same concentration of 0.2% Ropivacaine with an additional 4 mg/kg Dexamethasone was used for different TAP block procedures, and the US-ESP group had less postoperative pain and required fewer opioids than the OSTAP block group [ 92 ]. The addition of 0.5 mg/kg Esmolol to the local anesthetic for TAP block infiltration is more effective for pain management than the addition of 0.9% normal saline [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The time to request rescue analgesia was higher in the US-BRILMA group (845) than in the US-TAP group (759.33) [ 93 ]. The efficacy of erector spinae block and oblique subcostal transversus abdominis block was compared, and the mean pain of the two groups between 2 and 24 h differed, with the OSTAP block group reporting more pain experience (2.27 to 0.70) [ 92 ]). The US-TAPB block group had significantly lower resting VAS values than the two groups receiving PCIA with Sufentanil and Nalbuphineat 2, 6, 12, 24, and 48 h postop ( p < 0.05) (Han et al, 2022).…”
Section: Study Characteristicsmentioning
confidence: 99%